STUDY OF POTENCY DEVELOPMENT OF MARINE ECOTORISMTANGAH ISLAND PARIAMAN CITY WEST SUMATERA PROVINCE - Putra, Jefri Eliyas; Samiaji, Joko; Tanjung, Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract This research was conducted in March - April 2018 in Ketaping Beach, District ofPariaman City, West Sumatera Province. The study aims to identify the potential natural of area to be used as marine ecotourism, siteformulate strategies and assess to the role of stakeholders. The method used was survey method and station point was determined by purposive sampling. The result showed the Value of Conformity Index was 81.41 (Station I), 86.53 (Station II), 84.61 and (Station III). RespectivelyAn assessment of the strengths, weaknesses, opportunities and threats of potential development of marine ecotourism of Ketaping Beach was obtained from observations at research sites, interviews and questionnaires. Ketaping Beach has the potential as a marine ecotourism area based on natural beauty of nature, culinary tour, and cultural activities. Ketaping beach has gentle coastal and sandy area full with transition vegetation that can attract tourist attention. The development of marine ecotourism object in Ketaping Beach can be done by 1) Spatial and area arrangement by establishing zonation system for marine tourism activities and activities undertaken by the community towards marine ecotourism activities and coastal environment management, 2) Creating job, reducing poverty level and preserving nature, 3) Utilizing the potential of natural resources, history, culture, accessibility of the region to attract visitors through the development and development of marine tourism with the concept of ecotourism through the stages of promotion.Keywords: Potential, Marine Ecotourism, SWOT Analysis, Ketaping Beach